Tomato powder impedes the development of azoxymethane-induced colorectal cancer in rats through suppression of COX-2 expression via NF-?B and regulating Nrf2/HO-1 pathway - Tuzcu, Mehmet; Aslan, Abdullah; Tuzcu, Zeynep; Yabas, Mehmet; Bahcecioglu, Ibrahim Halil; Ozercan, Ibrahim Hanifi; Şahin, Kazım (Wiley, 2012)
Cancer is one of the leading causes of death worldwide. Since dietary factors have been connected to a reduced risk of a diversity of human cancers, in this study we investigated the effects of tomato powder (TP) on the development of azoxymethane (AOM)-induced colorectal cancer in Wistar rats, and possible mechanism(s) by which TP shows its chemopreventive activity. Here we show that TP added to feed at 5% rate decreases the rate of aberrant crypt foci (ACF) and reduces the development of adenocarcinoma and growth of AOM-induced colorectal cancer in rats. In addition, we demonstrate that TP supplementation shows its chemopreventive activities through inhibition of cyclooxygenase-2 (COX-2) expression via NF-?B pathway and promotion of apoptosis, as well as regulating Nrf2/HO-1 signaling pathway in colorectal tissue of AOM-treated rats. Our findings identify an intimate connection between dietary supplementation of TP and the decreased risk of colorectal cancer in rats, and suggest that consumption of TP would be a natural candidate for the prevention of colorectal cancer in men.
Keywords: Colorectal cancer; Cyclooxygenase-2; NF-?B; Oxidative stress; Tomato powder